2018
DOI: 10.17796/1053-4628-42.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Caries and Risk Factors in Vietnam

Abstract: This study indicated a high prevalence of caries and related risk factors such as low mother's educational level and inappropriate oral health behavior among kindergarten children in Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
4
12
1
3
Order By: Relevance
“…Previous studies conducted on Vietnamese children reported caries prevalences from 75% to 90%. DT/dt indices were about 6 in primary teeth and 2.5 in permanent teeth, similar to common population studies [ 44 , 45 , 46 ]. It did not seem that OI increases the prevalence of caries.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies conducted on Vietnamese children reported caries prevalences from 75% to 90%. DT/dt indices were about 6 in primary teeth and 2.5 in permanent teeth, similar to common population studies [ 44 , 45 , 46 ]. It did not seem that OI increases the prevalence of caries.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings confirm those of numerous studies that have found that Vietnam and other Southeast Asian countries have among the highest rates of ECC globally [11]. Other recent studies in Vietnam have found a greater likelihood of dental caries associated with a lower parent income, education and knowledge about oral health, a low child birthweight, the male gender, prolonged bottle-feeding and breastfeeding, the frequent consumption of sweets, poor toothbrushing habits, and limited access to dental care [17,18,19]. Many studies have found associations between caries and obesity, likely due to the common dietary risk factors, and the parenting practice of giving children frequent sweet snacks and drinks for behavior control [32].…”
Section: Discussionmentioning
confidence: 99%
“…A 2007 study of preschool children in Ho Chi Minh City found that 20.5% were overweight and 16.3% were obese [15]. The 2009 publication of the 1999 Vietnam’s National Oral Health Survey found that 85% of children aged 6–17 had tooth decay, a significantly higher prevalence and severity than that observed 10 years earlier [11,16]; and studies from 2015–2018 of children aged 2 to 6 in Vietnam found a prevalence of dental caries of around 90% [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of ECC in the world is about 60-90%, with the highest in Asia and Latin America [5]. In Vietnam, Nguyen YHT studies showed that ECC in children 3-5 years old accounted for 79.1% [6], and this rate of 4 years old children in Vo Truong Nhu Ngoc's study was 92% [7]. In addition, many studies have shown that the rate of ECC, S-ECC, dmft, and dmfs index in obese children was higher than in normal children [8][9][10].…”
Section: Introductionmentioning
confidence: 99%